2017
DOI: 10.1021/acs.jpcc.6b11576
|View full text |Cite
|
Sign up to set email alerts
|

Dislocation Core Structure at Finite Temperature Inferred by Molecular Dynamics Simulations for 1,3,5-Triamino-2,4,6-trinitrobenzene Single Crystal

Abstract: is an open access repository that collects the work of Arts et Métiers ParisTech researchers and makes it freely available over the web where possible. ABSTRACT: The dislocation core structures and elastic properties of the insensitive energetic molecular crystal 1,3,5-triamino-2,4,6-trinitrobenzene (TATB) are investigated as a function of pressure and temperature. A new method is proposed to compute the generalized stacking fault surfaces (noted γ-surfaces) and the complete second-order elastic tensor at fini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
62
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(70 citation statements)
references
References 41 publications
8
62
0
Order By: Relevance
“…Finally, compression behind the shock significantly increases barriers to homogeneous dislocation nucleation and glide. 24,25 These factors, combined with dynamic structural imperfections-whether relatively long lived (e.g., sliding defects) or induced transiently behind the shock-all tend to hinder or disrupt smooth dislocation glide. Several of these factors are present in flexible molecules but not rigid ones, or are likely behind explicit shock waves but not (or less so) for homogeneous, isothermal deformations.…”
Section: More Detailed Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…Finally, compression behind the shock significantly increases barriers to homogeneous dislocation nucleation and glide. 24,25 These factors, combined with dynamic structural imperfections-whether relatively long lived (e.g., sliding defects) or induced transiently behind the shock-all tend to hinder or disrupt smooth dislocation glide. Several of these factors are present in flexible molecules but not rigid ones, or are likely behind explicit shock waves but not (or less so) for homogeneous, isothermal deformations.…”
Section: More Detailed Analysismentioning
confidence: 99%
“…21 A monoclinic polymorph, also layered, has been reported recently at room temperature for pressures greater than 4 GPa. 22 The high degree of structural anisotropy leads to significant anisotropy in the mechanical, [23][24][25][26][27][28][29][30][31][32][33][34] thermal, [35][36][37][38][39][40][41][42][43][44][45][46][47] and spectroscopic 21 properties of the substance. See Figure 1 for a view of a TATB crystal and additional information pertinent to the shock simulation geometry and crystal orientations studied here (detailed below).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Atomic-based studies of the non-shock mechanical response of TATB have also been reported. 22,[24][25][26]28,29,[67][68][69] Because of the nature of the crystal packing, plasticity involving slip between basal planes in TATB (the crystal exhibits two inequivalent basal planes) is expected to occur with much 8 lower barriers to dislocation glide (i.e., stacking-fault energies), 70 in a fashion somewhat analogous to that in graphite, 71 compared to slip that occurs within a given molecular layer or that involves dislocation glide across multiple basal planes (both of which involve disrupting the intermolecular hydrogen-bonding network that exists within the layers). Indeed, using MD, very low stacking fault energies, and thus easy dislocation glide, were predicted for slip between adjacent basal planes both at zero kelvin 24 and at finite temperature.…”
Section: Introductionmentioning
confidence: 99%